Prediksi Tingkat Kepuasan Pelayanan Online Menggunakan Metode Algoritma C4.5 - Yuni Indah (SAFE-Network, 2022)
Online services are services that are carried out with the help of internet technology. This service allows various types of business to be completed easily without having to meet face-to-face with officers. Everything can run quickly and in real time. Especially during the Covid-19 pandemic as it is affecting the world, including Indonesia. Services that are carried out online are increasingly being carried out. Because it can help people to register online, so there is no need to meet face to face. make it easier for the public to register for the upcoming Adminduk and find out the increase or decrease in face-to-face services due to the pandemic. The data that is processed in this online service from 2019 to 2020 is about data about people who do not understand online services, negative community responses, positive community expectations. The method used is the C4.5 algorithm, which is one of the algorithms used to perform classification or segmentation or grouping and is predictive in nature. The advantages of this method are that it can produce a decision tree that is easy to interpret, has an acceptable level of accuracy, is efficient in handling type attributes. discrete and can handle both discrete and numeric type attributes. The results of this study can predict the value or level of community satisfaction in 2021 quickly and accurately. Therefore, this study can be used as a reference to determine the level of satisfaction in the population and civil registration office of Padang City. The method used is Prediction with C4.5 Algorithm using 14 attributes. The data used in this study is the data from the questionnaire research through the Disdukcapil database of 50 population data which has been presented in a csv file. The analysis in this study uses software tools Rapid Miner version 5.3000. The result of this research is to get 3 rules. So that this research can be used as a reference in predicting the level of online service satisfaction very well